Zornia brasiliensis: estudo de desreplicação, isolamento e atividade biológica de constituintes químicos - Nascimento, Yuri Mangueira do (2019)
Studies with extracts of plant species reflect on basic points, such as: drug development, information on efficacy and safety of those species with ethnomedicinal use, discovery of new therapeutic uses and contribution to the knowledge of the chemical-biological memory of plant species. The Zornia brasiliensis Vogel species belongs to the Leguminosae family, the Zornia genus has about 80 species throughout the world, distributed in several continents, such as: America, Africa, Oceania and Asia. Z. brasiliensis is popularly known as “urinary”, “urinana” and “carrapicho” and its popular use is reported as a diuretic and for the treatment of venereal diseases. It occurs in several states of Brazil, being abundant in the Northeast. This work aims to contribute to the chemical knowledge expansion of the genus Zornia through the isolation, identification and/or characterization of secondary metabolites from the species Z. brasiliensis. Aerial parts of Z. brasiliensis were collected in the municipality of Serra Branca, state of Paraíba. A specimen was deposited in the Herbarium Arruda Câmara (HACAM) of Universidade Estadual da Paraíba Campus I. After drying and milling, the plant material was macerated with 95% ethanol for 72 hours; this process was repeated four times, in order to obtain the crude ethanol extract (CEE). An aliquot of CEE (100.0g) was subjected to vacuum liquid chromatography (VLC) with silica as stationary phase and hexane, dichloromethane, ethyl acetate and methanol as mobile phase. An aliquot of the fraction of ethyl acetate-methanol 50% was subjected to column chromatography to carry out a prior fractionation of this fraction. An analytical method was then developed by HPLC-DAD, then transposed to a preparative scale, resulting in the isolation of nine compounds, roseoside, 7-methoxyflavanone, 7,4'- dimethoxyisoflavone, isoorientin-3'-O-methyl ether, isovitexine, glycosylated (Z)-Ocoumaric acid, glycosylated (E)-O-coumaric acid, dihydroelylotoside and zornioside, a C-glycosylated dihydrochalcona first reported in the literature. Another aliquot of the fraction ethyl acetate-methanol 50% was submitted to a specific saponin extraction methodology, which afterwards was subjected to preparative HPLC-DAD, leading to the isolation of Soyasaponin II. In addition, a methodology was developed by HPLC-ESI-DAD-MS/MS, enabling the dereplication and/or structural analysis by the putative characterization of 35 oleanan-triterpene saponins. Finally, this work contributes to the chemical and pharmacological knowledge of this species, once it has corroborated with Zornia's bioproduction of phenolic compounds through the Zornia brasiliensis phytochemical study, besides, it has demonstrated the cytotoxic potential of zornioside and has reported saponins in the Zornia genus for the first time, which is a class of secondary metabolites of relevant biological, pharmaceutical, cosmetic and agricultural importance.